On a Generalization of IF-Rings - Jawad Majid, Ali; Ramadan Mehdi, Akeel (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
In this paper, we present and investigate the notion of a right IREGF-ring as a proper generalization of the concept of a right IF-ring. A ring is defined as a right IREGF-ring if every injective right -module is Reg-flat. We provide numerous characterizations and explore various properties of right IREGF-rings.